Reassessing evidence of Moon–Earth dynamics from tidal bundles at 3.2 Ga (Moodies Group, Barberton Greenstone Belt, South Africa). Issue 5 (5th April 2022) - Heubeck, Christoph; Bläsing, Saskia; Drabon, Nadja; Eulenfeld, Tom; Grund, Marc Ulrich; Homann, Martin; Janse Van Rensburg, Deon; Köhler, Inga; Nabhan, Sami; Rabethge, Carolin; Voigt, Thomas; Zentner‐Joerges, Danielle
Abstract: Past orbital parameters of the Moon are difficult to reconstruct from geological records because relevant data sets of tidal strata are scarce or incomplete. The sole Archean data point is from the Moodies Group ( ca 3.22 Ga) of the Barberton Greenstone Belt, South Africa. From the time‐series analysis of tidal bundles from a well‐exposed subaqueous sand wave of this unit, Eriksson and Simpson ( Geology, 28, 831) suggested that the Moon's anomalistic month at 3.2 Ga was closer to 20 days than the present 27.5 days. This is in apparent accordance with models of orbital mechanics which place the Archean Moon in a closer orbit with a shorter period, resulting in stronger tidal action. Although this study's detailed geological mapping and section measuring of the site confirmed that the sandstone bed in question is likely a migrating dune, the presence of angular mud clasts, channel‐margin slumps, laterally aggrading channel fills and bidirectional paleocurrents in overlying and underlying beds suggests that this bedform was likely located in a nearshore channel near lower‐intertidal flats and subtidal estuarine bars; it thus carries risk of incomplete preservation. Repeated measurements of foreset thicknesses along the published traverse, measured perpendicular to bedding, failed to show consistent spectral peaks. Larger data sets acquired along traverses measured parallel to bedding along the 20.5 m wide exposure are affected by minor faulting, uneven outcrop weathering, changing illumination, weather, observer bias and show a low reproducibility. The most robust measurements herein confirm the periodicity peak of approximately 14 in the original data of Eriksson and Simpson ( Geology, 28, 831). Because laminae may have been eroded, the measurements may represent a lower bound of about 28 lunar days per synodic month. This estimate agrees well with Earth–Moon dynamic models which consider the conservation of angular momentum and place the Archaean Moon in a lower orbit around a faster‐spinning Earth.